Celebrating Scott Williams Birthday at Fresno-Merced Counties Legal Services - Watkins, Howard::::::::: (1980)
?, Alice Gutierrez, ?, Mary Ludy, Norma Herman, Verletz Hooks, Scott Williams Secretarial station; wooden coat rack